Bridging the gap: What have we done and what more can we do to reduce the burden of avoidable death in people with psychotic illness?. (15th January 2016) - Suetani, S.; Rosenbaum, S.; Scott, J. G.; Curtis, J.; Ward, P. B.
Abstract : Despite overwhelming evidence demonstrating a persisting gap in life expectancy between those with psychotic illness and the general population, there has been no widespread implementation of interventions to improve the physical wellbeing of people with psychotic illness. This article explores opportunities to 'Bridge the Gap' in life expectancy. We describe an Australian evidence-based intervention that has substantially improved the physical health of young people recently commenced on antipsychotic medication. Further epidemiological research, accompanied by cultural change within mental health services, is an essential precursor to the implementation of effective and sustainable lifestyle interventions. There are other relatively neglected areas of physical wellbeing for people with psychotic illness, such as screening and diagnosis of malignancies, which need more research and clinical attention. While there has been progress with intervention development and evaluation, translation of evidence-based short-term intervention studies into feasible and sustainable system-wide changes within routine mental health service settings remains a challenge. Developing an implementation framework to support such change is an urgent priority so as to bridge the persisting premature mortality in people living with psychotic illness.